The effect of intellectual capital on stock price and company value in manufacturing companies listed in Indonesia Stock Exchange 2008-2012 with size and leverage as moderating variables - Aprilina Suhermin (The Indonesian Accounting Review, 2014)
The intense competition in business world has prompted some companies to perform a variety of innovation in order to give the best value. Many companies have change the mindset of the management to knowledge-based business that becomes essential aspect in increasing the capital. The main purpose of this study is to examine the effect of intellectual capital on the stock price and the value of the company by doing moderation on the variables of size and leverage. Measurement of intellectual capital is using Value Added Intellectual Coefficient (VAIC). The stock price is measured based on the closing price and the company value is measured by using Tobins Q. The population of this study is the manufacturing companies listed on the Indonesia Stock Exchange. These results indicate that (1) intellectual capital can give a positive effect on the stock price (2) size and leverage are not moderating variables on the relationship between intellectual capital and stock price (3) intellectual capital does not have any effect on company value (4) size and leverage are not moderating variables on dealings with the value of the company's intellectual capital.